(3cJGH GdSQGFQs - (3CHh GdMSf Ydj Hf SYjO GdYScQis; (3YHO GdQMef Hf CMeO Hf QLH GdqSdGej GdHZOGOj Ke GdOeTbqj, CHh GdaQL, Rjf GdOjf,J (B795 (3g` s
(3ChdgG (B:s
(3CNHQfi CHh GdMSf Ydi Hf eMeO CHj GdeLO GdOeTbi s
(3BNQgG (B:s
)(3CNQ GdehLhO efg ef MOjK dQShd Gddg Udi Gddg Ydjg hSde (B) (3hef SeY SeY Gddg Hg(B) s
(3QhGjI CHh HcQ YHO Gddg Hf eMeO Hf eMeO Hf GdbHGHs
(3Ydi UaMI GdZdGa NW GdMGaX GHf MLQ GdYSbdGfi hYdjgG SeGYGJ HYVgG SfI (B707s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B118s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs